Nanomaterials - Toxicity and Risk Assessment 2015
DOI: 10.5772/60956
|View full text |Cite
|
Sign up to set email alerts
|

Medical Aspects of Nanomaterial Toxicity

Abstract: Nanosilver is the most popular and most studied nanomaterial, however, a family of nanomaterials is rapidly enlarging. They are used in various branches of industry and everyday life. In medicine new nanomaterials can be used either alone or in combination with other "classical" drugs, e.g. cytostatic drugs or antibiotics. They can be also used as diagnostic agents. A development of nanoparticles has led to a new combination of diagnostic and therapy -theranostic. Size of a particle makes a difference not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…There have been increasing concerns relating to their toxicity arising from their bioaccumulation in human body. It has been reported that they preferentially accumulate in the liver and spleen [29,30]. As a result, they cause many dysfunctions to these organs causing disruption to their body activities.…”
Section: Significance and Limitations Of Nanomaterialsmentioning
confidence: 99%
“…There have been increasing concerns relating to their toxicity arising from their bioaccumulation in human body. It has been reported that they preferentially accumulate in the liver and spleen [29,30]. As a result, they cause many dysfunctions to these organs causing disruption to their body activities.…”
Section: Significance and Limitations Of Nanomaterialsmentioning
confidence: 99%